Effect of Vitamin D Supplementation in Women with Pelvic Floor Dysfunction: A Systematic Review - Yanuaristi, Herdifitrianne Saintissa; Idhar, Syauqi Maulana; Rahman, Muhammad Nurhadi (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Objective: This review systematically analyzes and summarizes existing studies on the association between vitamin D supplementation and symptoms of Pelvic Floor Dysfunction (PFD) in women. Methods: We conducted a comprehensive literature search based on the Preferred Reporting Items for Systematic Review (PRISMA) Statements’ flow diagram for systematic review. Two independent reviewers searched five online databases using keywords to identify relevant studies from 2018-2023. Excluded were articles with populations other than women, case reports or case series, review papers, and studies that did not report vitamin D supplementation as a means of intervention in the study.Result: After identifying 2392 references, 13 studies were examined. Three studies explored the correlation between vitamin D supplementation and levator ani muscle strength, revealing a positive association. Results on vitamin D’s effect on urinary incontinence varied: five studies reported a negative correlation, while three showed significant improvement. Two studies indicated that vitamin D supplementation improved sexual function in the intervention group compared to the control group.Conclusion: Current evidence suggests that vitamin D supplementation is a potential strategy for the prevention and treatment of PFD in women, but relevant studies are severely available.Efek Suplementasi Vitamin D pada Wanita dengan Disfungsi Dasar Panggul: Tinjauan SistematikAbstrakTujuan: Tinjauan ini bertujuan untuk menganalisis secara sistematis studi yang ada dan meringkas data yang menunjukkan hubungan antara suplementasi vitamin D dan wanita dengan gejala disfungsi dasar panggul.Metode: Pada penelitian ini, dilakukan pencarian literatur yang komprehensif berdasarkan diagram alir Preferred Reporting Items for Systematic Review (PRISMA) untuk tinjauan sistematis. Dua pengulas independen mencari lima basis data daring menggunakan kata kunci untuk mengidentifikasi studi yang relevan dari tahun 2018 – 2023. Artikel dengan populasi selain wanita, laporan kasus atau seri kasus, makalah ulasan, dan studi yang tidak melaporkan suplementasi vitamin D sebagai sarana intervensi dalam studi dikecualikan.Hasil: Setelah mengidentifikasi 2394 referensi dan 13 studi ditinjau. Tiga studi melaporkan korelasi antara suplementasi vitamin D dan kekuatan otot levator ani, mengungkapkan hubungan positif. Namun, hasil mengenai dampak vitamin D pada inkontinensia urin bervariasi: lima studi melaporkan korelasi negatif, sementara tiga menunjukkan perbaikan signifikan. Dua studi menunjukkan bahwa suplementasi vitamin D meningkatkan fungsi seksual pada kelompok intervensi dibandingkan dengan kelompok kontrol.Kesimpulan: Bukti saat ini menunjukkan bahwa suplementasi vitamin D merupakan strategi pencegahan dan pengobatan yang potensial untuk wanita dengan disfungsi dasar panggul, tetapi penelitiannya masih sangat terbatas.Kata kunci: Vitamin D, Disfungsi Dasar Panggul, Prolaps, Inkontinensia